On the wear characteristics of leaded aluminium bearing alloys - Pathak J.P.; Tiwari S.N.; Malhotra S.L. (My University, 2025)
The wear characteristics of a series of leaded aluminium bearing alloys have been studied under dry sliding conditions under a room atmosphere using a pin-on-disc-type wear testing machine. The wear volume has been measured as a function of the alloy composition, sliding distance, normal load and sliding velocity. Optical and scanning electron microscopic examinations of the test specimen, wear track and wear debris have been carried out to aid in the elucidation of the wear mechanisms. It has been observed generally that the wear rate decreases with increasing lead content and hardness of aluminium-based alloys. © 1986.